Function spaces : (World Scientific, 2003)
This volume discusses the following topics: convex analysis, operator theory, interpolation theory, theory of real functions, theory of analytic functions, bifurcation theory, Fourier analysis, functional analysis, measure theory, geometry of Banach spaces, history of mathematics.